The cat sitter and the canary : a Dixie Hemingway mystery - Clement, Blaize; Clement, John, 1962- (Clement, Blaize. Dixie Hemingway mysteries., 2016)
"This time out, Dixie's got a furry partner-in-crime, an irascible Lhasa Apso named Charlie. They've just arrived at the home of one of Dixie's regular clients to check in on Franklin, a mackerel tabby with avocado-green eyes and a luxuriant coat the color of dried beach grass. Despite a couple of bumps in the road (Franklin seems to be hiding in one of his favorite cubby holes, and Charlie scratches up the parlor door trying to get to the other side), everything else is perfectly normal. That is, until the next day, when Dixie discovers a dead body on the other side of that parlor door, along with a note that seems to suggest she had something to do with it. Soon, there's another victim, and then another note, and Dixie quickly finds herself caught in a maze of mystery and danger, where all the clues have her name written all over them, and where she must find the murderer. . . before he finds her"--